Heart failure with preserved ejection fraction induces molecular, mitochondrial, histological, and functional alterations in rat respiratory and limb skeletal muscle. (6th February 2015) - Bowen, T. Scott; Rolim, Natale P. L.; Fischer, Tina; Bækkerud, Fredrik H.; Medeiros, Alessandra; Werner, Sarah; Brønstad, Eivind; Rognmo, Oivind; Mangner, Norman; Linke, Axel; Schuler, Gerhard; Silva, Gustavo J. J.; et al.
<x xml:space="preserve">Abstract</x> Aims Peripheral muscle dysfunction is a key mechanism contributing to exercise intolerance (i.e. breathlessness and fatigue) in heart failure patients with preserved ejection fraction (HFpEF); however, the underlying molecular and cellular mechanisms remain unknown. We therefore used an animal model to elucidate potential molecular, mitochondrial, histological, and functional alterations induced by HFpEF in the diaphragm and soleus, while also determining the possible benefits associated with exercise training. Methods and results Female Dahl salt‐sensitive rats were fed a low (CON; n = 10) or high salt (HFpEF; n = 11) diet of 0.3% or 8% NaCl, respectively, or a high salt diet in combination with treadmill exercise training (n = 11). Compared with low‐salt rats, high‐salt rats developed (P < 0.05) HFpEF. Compared with CON, the diaphragm of HFpEF rats demonstrated (P < 0.05): a fibre type shift from fast‐to‐slow twitch; fibre atrophy; a decreased pro‐oxidative but increased anti‐oxidant capacity; reduced proteasome activation; impaired in situ mitochondrial respiration; and in vitro muscle weakness and increased fatigability. The soleus also demonstrated numerous alterations (P < 0.05), including fibre atrophy, decreased anti‐oxidant capacity, reduced mitochondrial density, and increased fatigability. Exercise training, however, prevented mitochondrial and functional impairments in both the diaphragm and soleus (P < 0.05). Conclusion Our findings are the first to demonstrate that HFpEF induces significant molecular, mitochondrial, histological, and functional alterations in the diaphragm and soleus, which were attenuated by exercise training. These data therefore reveal novel mechanisms and potential therapeutic treatments of exercise intolerance in HFpEF.